The effects of muscle energy on low back pain: a 3D analysis of running biomechanics - Drapeaux, A.; Hurdelbrink, J. (International Journal of Kinesiology & Sports Science, 2021)
Background: Muscle energy technique (MET) is asn osteopathic treatment technique that is utilized frequently in the clinical setting, yet the overall effectiveness is minimally supported within literature. MET is an osteopathic technique that involves an isometric contract relax technique intended to improve alignment and enhance neuromuscular education. Objective: The purpose of this study was to determine the effectiveness of MET on running kinetics on subjects with low back pain. Method: A quasi-experimental research design was implemented and subjects, all of whom either had a history of or currently experience low back pain, underwent pre-intervention data collection of: anthropometric measurements, medical history, dorsaVi 3D running analysis, and a musculoskeletal and neurological clinical exam. Subjects underwent 6 weeks of isolated lumbo-pelvic MET at a frequency of twice a week, and were instructed to avoid all other treatment. Post-intervention data collected included a clinical exam and another dorsaVI running analysis. Results: Data was analyzed including: pre and post-treatment initial peak acceleration, ground contact time, and ground reaction force. A paired t-test comparing pre and post mean kinetic changes demonstrated the following p values: initial peak acceleration p = .80, ground contact time p = .96, and ground reaction force p = .68. Conclusion: This study demonstrated that isolated MET treatment is not statistically significant for changing 3D kinetic running variable in subjects with low back pain. Clinical Implications: Recommend healthcare providers to use a multi-treatment approach for low back pain. Future research should include a control group and larger sample size.